Relationship enhancement methods - Cook, Barbara (Encyclopedia of Autism Spectrum Disorders, 2018)
Keywords: dept.cmd

Interpersonal supports - Cook, Barbara (Encyclopedia of Autism Spectrum Disorders, 2018)
Keywords: dept.cmd

Masked-Speech Recognition and Self-Reported Functional Listening in Autistic Young Adults - Wasiuk, Peter; Cook, Barbara; Irwin, Julia (Journal of Speech Language and Hearing Research, 2025)
Keywords: Active listening; Audiology; Autism; Cognitive psychology; Communication; Developmental psychology; Medicine; Perception; Psychology; Speech perception; dept.cmd; dept.psy

A facilitated natural mentoring program: Young adults with autism learn to negotiate college life in a class with university students - Cook, Barbara; Weiss, Deborah; Hodge, Virginia (The ASHA Leader, 2017)
Young adults with autism learn to negotiate college life in a class with university students. © 2017 American Speech-Language-Hearing Association.
Keywords: dept.cmd

Transdisciplinary Approach Practicum for Speech-Language Pathology and Special Education Graduate Students - Weiss, Deborah; Cook, Barbara; Eren, Ruth (Journal of Autism and Developmental Disorders, 2020)
Speech-language pathology and special education graduate student teams participated in an intensive summer practicum for social communication skills with children with autism spectrum disorders, utilizing a transdisciplinary approach that aligned to the frameworks utilized for implementation science. Questionnaires measuring transdisciplinary approach knowledge and comfort level were administered pre/post-practicum. Results of the questionnaires, written daily team reflections, course evaluations, and a focus group interview indicated an increase in all measures, including an increased knowledge of TA, increased understanding and comfort level with the other discipline, and a higher level of confidence and openness in working collaboratively utilizing a transdisciplinary approach. © 2020, Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: Academic Performance; Article; Autism Spectrum Disorder; Autism spectrum disorder; Child; Collaborative teaming; Communication; Education, Special; Female; Humans; Implementation science; Interdisciplinary Research; Interprofessional collaboration; Male; Special education; Speech-Language Pathology; Speech-language pathology; Students, Health Occupations; Surveys and Questionnaires; Transdisciplinary; academic achievement; autism; child; comfort; communication skill; course evaluation; dept.cmd; dept.sed; education; female; graduate student; health student; human; implementation science; interdisciplinary education; interdisciplinary research; interpersonal communication; interview; knowledge; male; peer-reviewed; pretest posttest design; priority journal; procedures; professional development; psychology; quantitative analysis; questionnaire; social competence; special education; speech disorder; teacher; training

Peer mentors for students with ASD on college campuses - Cook, Barbara; Weiss, Deborah (Encyclopedia of Autism Spectrum Disorders, 2018)
Keywords: dept.cmd

Babysitter training guide for families with individuals with ASD - Bean, K; Neers, K; Cook, Barbara; Eren, R (Encyclopedia of Autism Spectrum Disorders, 2020)
The Second Edition of this major reference work expands its coverage and continues to break new ground as an electronic resource for students, educators, researchers, and professionals. Comprehensive in breath and textbook in depth, the Second Edition of the Encyclopedia of Autism Spectrum Disorders serves as a reference repository of knowledge in the field as well as a regularly updated conduit of new knowledge long before such information trickles down from research to standard textbooks. The Second Edition of the Encyclopedia digests and presents new and updated information for readers who need to stay current with the latest research and clinical practices, including advances in neurobiology and genetics, diagnostic instruments and assessment tests, pharmaceutical treatments, and behavioral, speech and language, and other rehabilitative therapies. The Second Edition of the Encyclopedia covers topics across the following major conceptual areas of ASD and PDDs, including: Research trends and findings Behavior/speech Communication TreatmentsEducation Taking advantage of the techniques offered by the electronic medium, the Second Edition of the Encyclopedia of Autism Spectrum Disorders offers an extensive cross-referencing system facilitating search and retrieval of information. This unique, comprehensive Second Edition of the Encyclopedia of Autism Spectrum Disorders is an essential reference for advanced undergraduate and graduate students as well as researchers, professors, clinicians, and other practitioners across such related disciplines as developmental psychology, child and adolescent psychiatry, social work, child and school psychology, behavioral therapy, and sociology of education.
Keywords: dept.cmd

Electrophysiological Indices of Audiovisual Speech Perception in the Broader Autism Phenotype. - Irwin, Julia; Avery, Trey; Turcios, Jacqueline; Brancazio, Lawrence; Cook, Barbara; Landi, Nicole (Brain sciences, 2017)
When a speaker talks, the consequences of this can both be heard (audio) and seen (visual). A novel visual phonemic restoration task was used to assess behavioral discrimination and neural signatures (event-related potentials, or ERP) of audiovisual processing in typically developing children with a range of social and communicative skills assessed using the social responsiveness scale, a measure of traits associated with autism. An auditory oddball design presented two types of stimuli to the listener, a clear exemplar of an auditory consonant-vowel syllable /ba/ (the more frequently occurring standard stimulus), and a syllable in which the auditory cues for the consonant were substantially weakened, creating a stimulus which is more like /a/ (the infrequently presented deviant stimulus). All speech tokens were paired with a face producing /ba/ or a face with a pixelated mouth containing motion but no visual speech. In this paradigm, the visual /ba/ should cause the auditory /a/ to be perceived as /ba/, creating an attenuated oddball response; in contrast, a pixelated video (without articulatory information) should not have this effect. Behaviorally, participants showed visual phonemic restoration (reduced accuracy in detecting deviant /a/) in the presence of a speaking face. In addition, ERPs were observed in both an early time window (N100) and a later time window (P300) that were sensitive to speech context (/ba/ or /a/) and modulated by face context (speaking face with visible articulation or with pixelated mouth). Specifically, the oddball responses for the N100 and P300 were attenuated in the presence of a face producing /ba/ relative to a pixelated face, representing a possible neural correlate of the phonemic restoration effect. Notably, those individuals with more traits associated with autism (yet still in the non-clinical range) had smaller P300 responses overall, regardless of face context, suggesting generally reduced phonemic discrimination.
Keywords: Article; Audiovisual speech perception; Broader autism phenotype; Development; ERP; audiovisual aid; audiovisual equipment; audiovisual speech perception; autism; behavior; broader autism phenotype; child; clinical article; dept.cmd; dept.hls; dept.psy; development; electrophysiology; female; human; male; participant observation; phenotype; social adaptation; social competence; speech perception; stimulus; vision test

College Access, Success and Equity for Students on the Autism Spectrum. - Accardo, Amy L; Bean, Kimberly; Cook, Barbara; Gillies, Ann; Edgington, Rebecca; Kuder, S Jay; Bomgardner, Estyr M (Journal of autism and developmental disorders, 2019)
College may be considered a gateway to success, yet access to college is limited for young adults with autism. Given the research recommendations to elicit student experiences and to communicate among universities to improve college access, success, and equity, the present study examined the questions: What factors are perceived as pathways to success or barriers to success by college students on the autism spectrum? What university provided accommodations and/or support services do they prefer? Participants from four universities completed surveys and semi-structured interviews. Findings from the multi-university study suggest the need to provide transition planning and systematic non-academic social and emotional supports from the start of the college experience as well as specific training for faculty, staff, and peers.
Keywords: *Academic Success; *Autism Spectrum Disorder/rh [Rehabilitation]; *Mainstreaming, Education/sn [Statistics & Numerical Data]; *Universities/sn [Statistics & Numerical Data]; Academic Success; Accommodations; Adolescent; Article; Autism Spectrum Disorder; Autism Spectrum Disorder/px [Psychology]; Autism spectrum disorder; College; Female; Humans; Mainstreaming, Education; Male; Mental health; Students; Students/px [Psychology]; Students/sn [Statistics & Numerical Data]; Universities; University; Young Adult; academic success; adolescent; adult; autism; college; college student; dept.cmd; dept.sed; disability; executive function; female; financial management; follow up; health equity; human; longitudinal study; male; mental health care; motivation; peer-reviewed; priority journal; psychology; self concept; semi structured interview; social network; social support; student; student attitude; university; young adult